Effects of dietary hot water extracts of Chlorella vulgaris on muscle component, non-specific immunity, antioxidation, and resistance to non-ionic ammonia stress in Pacific white shrimp Litopenaeus vannamei - Zhang, Dan; Shi, Shuyi; Jia, Xuying; Zhou, Wenli; Sun, Xiaoyu; Han, ChaoJie; Lu, Yunliang (Frontiers in Marine Science, 2024)
Hot water extract of Chlorella vulgaris (CVE) is a biologically substance that enhances organism's immune function and antioxidative capacity. This study evaluated the effect of supplementation with various concentrations of CVE on muscle nutritional components, non-specific immunity, antioxidation, and resistance to non-ionic ammonia (NH3-N) stress in Litopenaeus vannamei over 45 days using diets supplemented with CVE at five different concentrations (0%, 0.5%, 1%, 5%, 10%, and 15%). Results demonstrated that dietary CVE supplement (0.5-15% groups) increased the content of amino acid and unsaturated fatty acid. Specifically, fresh and sweet amino acids (Asp, Glu) significantly increased (P < 0.05) in shrimp fed the 1% CVE diet, reaching 18.12 g/kg and 33.08 g/kg, respectively. Bitter amino acids (Leu) and Hypoxanthine (Hx) significantly decreased (P < 0.05) in shrimp fed the 1% CVE diet, at 10.56 g/kg and 10.56 ug/g. CVE supplementary enhanced the activities of acid phosphatase, alkaline phosphatase, and nitric oxide synthase while decreasing malondialdehyde levels. Shrimp fed with a 1% CVE diet exhibited significantly higher enzyme activity than the control group under NH3-N conditions (P < 0.05). Overall, this study demonstrated that 1% CVE as a feed additive significantly improved the muscle mass, boosted immunity and reduced the stress response to NH3-N in L. vannamei. This research provides a valuable reference for the application of CVE as a feed additive in crustacean aquaculture.